2012
DOI: 10.1159/000337338
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Volume Status in Asymptomatic Haemodialysis and Peritoneal Dialysis Outpatients

Abstract: Background: The majority of haemodialysis (HD) patients gain weight between dialysis sessions and thereby become volume overloaded, whereas peritoneal dialysis (PD) is a more continuous technique. Cardiovascular mortality and hypertension is increased with both treatment modalities. We therefore wished to compare volume status in PD and HD to determine whether PD patients are chronically volume overloaded, as a risk factor for cardiovascular mortality. Study Design, Setting and Participants:We retrospectively … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
44
1

Year Published

2013
2013
2025
2025

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 54 publications
(47 citation statements)
references
References 57 publications
2
44
1
Order By: Relevance
“…Previous reports have shown that while haemodialysis patients have a change in hydration status with dialysis sessions, PD patients generally experience volume expansion with an increased ECW/TBW ratio [10]. However, this ECW expansion does not necessarily reflect increased plasma volume, as ECW excess does not increase peritoneal ultrafiltration [7] or preserve residual renal function [11].…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports have shown that while haemodialysis patients have a change in hydration status with dialysis sessions, PD patients generally experience volume expansion with an increased ECW/TBW ratio [10]. However, this ECW expansion does not necessarily reflect increased plasma volume, as ECW excess does not increase peritoneal ultrafiltration [7] or preserve residual renal function [11].…”
Section: Discussionmentioning
confidence: 99%
“…Although none of these studies used PD as a comparison group, it is plausible that some of the known benefits of HHD over facility HD also apply when comparing HHD with PD. Indeed, although PD allows constant ultrafiltration, total fluid removal can sometimes be limited and possibly, lead to hypervolemia and hypertension (44)(45)(46)(47). Comparison of clearance quality between PD and HD is limited, although it seems reasonable to postulate that patients treated with long or long/frequent HHD receive a higher dialysis dose than most patients on PD.…”
Section: Discussionmentioning
confidence: 99%
“…Multifrequency bioelectrical impedance analysis (MF-BIA) measurements were made after dialysis (InBody 720 Body Composition Analysis, Biospace, Seoul, South Korea) [18], using tetrapolar 8-point tactile electrodes [19]. Patients with cardiac pacemakers, implantable defibrillators, amputees and those unable to stand on the bio-impedance device were excluded.…”
Section: Methods and Patientsmentioning
confidence: 99%